2023
DOI: 10.1007/s12662-023-00893-8
|View full text |Cite
|
Sign up to set email alerts
|

Bewegungsförderung bei sozial benachteiligten Frauen

Abstract: Zusammenfassung Hintergrund Das Projekt „Bewegung als Investition in Gesundheit“ (BIG) – ein partizipatives Projekt im kommunalen Setting – wurde 2005 entwickelt, um benachteiligten Frauen den Zugang zu körperlich-sportlicher Aktivität zu erleichtern. Seitdem wurde BIG deutschlandweit auf 17 Kommunen übertragen. Ziel Es wird untersucht, ob im BIG-Projekt sozial benachteiligte Frauen erreicht und an Bewegungskurse gebunden werden können. Zudem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The transferability of the BIG approach was observed among the examined communities ( 37 ). Furthermore, quantitative data collected at two BIG sites between 2006 and 2013 reported improved health status and increased PA among participating women compared to before BIG participation ( 38 ). The present study adds to this existing evidence that many of these effects ( 35 38 ) were also observed among long-term participants and had positive effects on their physical, mental, and social health.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The transferability of the BIG approach was observed among the examined communities ( 37 ). Furthermore, quantitative data collected at two BIG sites between 2006 and 2013 reported improved health status and increased PA among participating women compared to before BIG participation ( 38 ). The present study adds to this existing evidence that many of these effects ( 35 38 ) were also observed among long-term participants and had positive effects on their physical, mental, and social health.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, quantitative data collected at two BIG sites between 2006 and 2013 reported improved health status and increased PA among participating women compared to before BIG participation ( 38 ). The present study adds to this existing evidence that many of these effects ( 35 38 ) were also observed among long-term participants and had positive effects on their physical, mental, and social health. In addition, we identified further effects on the health behavior of participating women, such as changes in PA and dietary behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations